Flight of the Conchords. The complete second season [videorecording (DVD)] - Clement, Jemaine; Clement, Jemaine; McKenzie, Bret; McKenzie, Bret (HBO Home Entertainment ; Distributed by Warner Home Video, 2009)
Despite living as Big Apple bohemians for over a year, Jermaine Clement and Bret McKenzie remain hopelessly out of place in Manhattan. Will Season 2 bring them excitement, romance, and the elusive music gig?